Marxism and the city - Katznelson, Ira.; Oxford eBooks (Oxford : Clarendon, 1992)
An assessment of the scholarship on cities that has developed within Marxism in the past quarter of a century to show how some of the most important weaknesses in Marxism as a social theory can be remedied by forcing it to engage seriously with cities and spatial concerns.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sociology, Urban; Marxian school of sociology; Electronic books